A ARTE E A COMPETÊNCIA LEITORA: UMA EXPERIÊNCIA INTERDISCIPLINAR SÃO BERNARDO DO CAMPO 2016 Dissertação apresentada em cumprimento às exigências do Programa de Pós-Graduação em Educação da Universidade Metodista de São Paulo para obtenção do grau de Mestre. Orientação: Profa. - OREFICE, ÉRICA FELÍCIO DE CARVALHO OREFICE (2016)
This research deals with Art’s role in educational context. Initially It puts the researcher in Art Education environment through self-portrait report presenting their concern with Brazilian education and the Art´s role in this scenario. In its first chapter presents the trajectories of Art Education in Brazil with an historical account of its construction and constitution. In its second chapter, It discusses the Art itself talking about various languages of Art and considering the Art reader competence of verbal and non-verbal. In its last chapter recounts experiences with teaching and learning processes in classroom dealing readings possibilities in Art and interdisciplinary experiences from Art with Mathematics, Chemistry, Physics and Philosophy, emphasizing the difficulties and richness of these experiences. The main researcher driver was to answer the question: Are teachers that lived formative experiences mediated image, able to rethink the teaching of their expertise areas, proposing to students also different ways to exhibit their knowledge and their feelings in more comprehensive learning perspective? In its final remarks reflects on obtained results in classroom presenting the differential achieved with reinforcement learning experiences through Art, offering a way to answer the asked question and inferring about other issues related to reading capacity through images. This researche acknowledges that much remains to be done in relation to education and that this is an evolving and continuous process, a form of construction. It also shows the possibility of continuing and expanding this work, recognizing that not only the student should be played, but also the Art Educator.